2004
DOI: 10.1590/s1677-04202004000100006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of salt stress on growth, nitrate reduction and proline and glycinebetaine accumulation in Prosopis alba

Abstract: Prosopis alba (algarrobo) is one of the most important salt-tolerant legumes used in the food and furniture industries. The effects of salinity on some growth and physiological parameters in algarrrobo seedlings were investigated. 17-Day-old seedlings were subjected to three salt treatments by adding NaCl to the growth medium in 50 mmol.L-1 increments every 24 h until the final concentrations of 0, 300 and 600 mmol.L-1 were reached. Only the highest NaCl concentration affected all of the considered parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
79
1
18

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 54 publications
13
79
1
18
Order By: Relevance
“…However, under salt-stress conditions, NO 3 -contents were significantly reduced in shoot, mainly in seedlings from non-aged and primed seeds ( Figure 4A). These results suggest that salt stress negatively affects shoot NO 3 -accumulation, which corroborates the results by Meloni et al (2004), who reported that salinity treatments in Prosopis alba also leads to shoot NO 3 -decreases. The Cl -content increased in seedling shoot from non-aged and artificially aged seeds subjected to salt stress, and these contents were highest as a function of seed priming (Figures 4C-D).…”
Section: Resultssupporting
confidence: 92%
“…However, under salt-stress conditions, NO 3 -contents were significantly reduced in shoot, mainly in seedlings from non-aged and primed seeds ( Figure 4A). These results suggest that salt stress negatively affects shoot NO 3 -accumulation, which corroborates the results by Meloni et al (2004), who reported that salinity treatments in Prosopis alba also leads to shoot NO 3 -decreases. The Cl -content increased in seedling shoot from non-aged and artificially aged seeds subjected to salt stress, and these contents were highest as a function of seed priming (Figures 4C-D).…”
Section: Resultssupporting
confidence: 92%
“…Generally, compatible solutes such as proline, sucrose, trehalose and polyols, and quaternary compounds such as glycinebetaine, protect plants from stress through different mechanisms, which include contributions to cellular osmotic adjustment, acceleration of reactive oxygen species scavenging systems, protection of membrane integrity, and stabilization of enzymes/ proteins (Ashraf and Foolad, 2007). Compatible solutes were originally thought to function as cytosolic osmotica involved in cellular osmoregulation (Hasegawa et al, 2000;Meloni et al, 2004). Consistent with this view, the increase in cellular osmolality that results from the accumulation of non-toxic, osmotically active solutes is accompanied by a reduced efflux of water from cells or even an influx of water into them, thus providing the turgor pressure necessary for cell expansion (Wyn Jones and Storey, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Farias et al (2009) claim that salinity reduces the activity of the ions in solution and alters the processes of absorption, transport, assimilation and distribution of nutrients in the plant. Among these ions, nitrate is the most affected (Aragão et al, 2010;Meloni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%